Drug-induced eRF1 degradation promotes readthrough and reveals a new branch of ribosome quality control - Lukas-Adrian Gurzeler; Marion Link; Yvonne Ibig; Isabel Schmidt; Olaf Galuba; Julian Schoenbett; Christelle Gasser-Didierlaurant; Christian N. Parker; Xiaohong Mao; Francis Bitsch; Markus Schirle; Philipp Couttet; et al. (Cell Reports, 2023)
Summary: Suppression of premature termination codons (PTCs) by translational readthrough is a promising strategy to treat a wide variety of severe genetic diseases caused by nonsense mutations. Here, we present two potent readthrough promoters—NVS1.1 and NVS2.1—that restore substantial levels of functional full-length CFTR and IDUA proteins in disease models for cystic fibrosis and Hurler syndrome, respectively. In contrast to other readthrough promoters that affect stop codon decoding, the NVS compounds stimulate PTC suppression by triggering rapid proteasomal degradation of the translation termination factor eRF1. Our results show that this occurs by trapping eRF1 in the terminating ribosome, causing ribosome stalls and subsequent ribosome collisions, and activating a branch of the ribosome-associated quality control network, which involves the translational stress sensor GCN1 and the catalytic activity of the E3 ubiquitin ligases RNF14 and RNF25.